Human Resource Business Partners: HR Strategy, Business Model and Leadership (Literature Review) - Siska Yuli Anita; Yuntina, Lily; Sundari, Pipit; Sugiarti, Sugiarti; Eko Widodo, Rintis (Siber Journal of Advanced Multidisciplinary, 2024)
Literature review article related to human resource business partners: HR strategy, business model and leadership (literature review) is a scientific literature article in the scope of human resource management science. The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The approach used in this study is descriptive qualitative. The data collection technique uses literature studies. Data were obtained from previous studies that are relevant to this study and sourced from academic online media such as the Scopus Journal, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this article are: 1) HR strategy related to Human Resource Business Partners; 2) Business Model related to Human Resource Business Partners; and 3) Leadership related to Human Resource Business Partners.